Systematic Analysis of Potential Marine Renewable Energy for Coastal Ecological Balance on Bawean Island: A Review - Sari, Wanda Rulita; Gunawan, Gunawan; Surjosatyo, Adi; Muzhoffar, Dimas Angga Fakhri (Institut Teknologi Sepuluh Nopember, 2024)
Bawean Island displays significant natural potential with abundant natural resources and natural beauty that is attractive for tourism and industrial development. However, this potential is threatened by various environmental and socio-economic problems such as limited availability of clean water, erosion of coastal structures, accumulation of rubbish, economic challenges, and low levels of community education. To overcome these challenges, an integrated and sustainable approach is needed that involves the government, community, and other related parties in sustainable natural resource management and considers ecological, economic, and social aspects. Systematic analysis is carried out to understand the potential of coastal natural resources and the problems that threaten the ecosystem. An integrated and sustainable approach is needed, involving collaboration between government, society, and related parties. The integration of new technologies, including renewable energy technologies, was identified as a potential solution to several specific problems, such as waste management and clean water supply. An integrated and sustainable approach is analyzed by involving collaboration between government, society, and related parties. With collaboration and a deep understanding of the challenges and potential of Bawean Island, it is hoped that a sustainable coastal ecological balance can be achieved for the welfare of the environment and local communities.